Sistem Pengaturan Pencahayaan pada Budidaya Jamur Tiram Berbasis Arduino Uno Dengan Metode Fuzzy Logic - Dewatama, Denda; Fauziyah, Mila; Jannah, Nur Kholifatu (Program Studi Teknik Elektro Universitas Khairun, 2022)
Light has an important role for oyster mushroom cultivation in order to get optimal mushroom growth. The light needed by mushrooms ranges from 150-250 lux. In addition, temperature and humidity also affect the growth of fungi. This research was conducted to examine what color spectrum is suitable for mushrooms, and to make an automatic light control device to make it easier for farmers to maintain lighting stability in mushroom kumbung. This lighting control system uses an LDR sensor as a measure of the intensity of light in the space around the mushroom and also uses Arduino Uno as a tool control. The study was conducted experimentally for 4 days, the color spectrum suitable for mushrooms is yellow because at the time the research was conducted the results of the fungus were 13 cm wide at the longest, 243 grams in total weight, and had the brightest color compared to blue and red. The lighting stability with a set point of 200 lux is set using the FLC algorithm with 5 error memberships, 5 Delta error memberships, and also Single Tone. Generates a system response from fuzzy logic as follows: tr = 3 seconds, tp = 6 seconds, %overshoot = 0.04%, ts = 13 seconds, ess = Ã‚Â±4%.Ã‚Â